2015
DOI: 10.1007/s11030-015-9621-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anticancer activity of novel fused pyrimidine hybrids of myrrhanone C, a bicyclic triterpene of Commiphora mukul gum resin

Abstract: Myrrhanone C [8(R)-3-oxo-8-hydroxypolypoda-13E,17E,21-triene], a bicyclic triterpene isolated from the gum resin of Commiphora mukul, has been chemically transformed to synthesize a series of ten novel pyrimidine hybrids in good to excellent yields. The synthesized compounds (2-22) were evaluated for their anticancer potential against a panel of six cancer cell lines, namely A-549 (lung), Hela (cervical), MCF-7 (breast), ACHN (renal), Colo-205 (colon) and B-16 (mouse melanoma) by employing the MTT assay. In ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…141a (IC 50 = 9.5 μM) and 141b (IC 50 = 7.7 μM) showed the best activity against A-549 cancer cell line due to induction of apoptosis at the G0/G1 phase of the cell cycle. SAR suggested that 4chloro and 4-bromo pyrimidine hybrid have 5-6 times more activity against the A-549 whereas 2-3 times more activity against the other abovementioned cell lines than the parent compound [144]. Novel azacalix [2]aren e [2] pyrimidines were screened against the MCF-7 cancer cell line.…”
Section: Miscellaneous Fused Ring Pyrimidine Derivativementioning
confidence: 99%
“…141a (IC 50 = 9.5 μM) and 141b (IC 50 = 7.7 μM) showed the best activity against A-549 cancer cell line due to induction of apoptosis at the G0/G1 phase of the cell cycle. SAR suggested that 4chloro and 4-bromo pyrimidine hybrid have 5-6 times more activity against the A-549 whereas 2-3 times more activity against the other abovementioned cell lines than the parent compound [144]. Novel azacalix [2]aren e [2] pyrimidines were screened against the MCF-7 cancer cell line.…”
Section: Miscellaneous Fused Ring Pyrimidine Derivativementioning
confidence: 99%
“…In this context, natural products are promising and efficient starting materials for the discovery and development of new drugs, particularly in the anticancer field; more than 70% of the current anticancer drugs are natural or derived of natural products with a variety of structures and mechanisms of action that would increase when they are combined into new hybrid entities . The synergistic or additive effect of those new chemical entities is a promising approach in diverse diseases, particularly in cancer therapy, for example, to avoid resistances or discover new applications for future treatments …”
mentioning
confidence: 99%
“…The anticancer potential against the HCT-116 cell line has also been demonstrated by N-acylated benzenesulfonamides, which contained at the benzene ring the 1-naphthylmethylthio substituent and the sulfonamidic nitrogen atom bonded to acetic acid or cinnamic acid residues [30]. Similarly, fused pyrimidine hybrids of myrrhanone C and Argentatins A-C showed noticeable anticancer activity against several human cancer cell lines [31,32]. The main goal of this study was to assess the sulfonamide derivatives with proven anticancer activities against human colon cancer (HCT-116) using a chromatographic approach.…”
Section: Introductionmentioning
confidence: 96%